Clinical Predictors and Prognostic Impact of Recovery of Wall Motion Abnormalities in Takotsubo Syndrome: Results From the International Takotsubo Registry - Stjepan Jurisic; Sebastiano Gili; Victoria L. Cammann; Ken Kato; Konrad A. Szawan; Fabrizio D'Ascenzo; Milosz Jaguszewski; Eduardo Bossone; Rodolfo Citro; Annahita Sarcon; L. Christian Napp; Jennifer Franke; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2019)
Background Left ventricular (LV) recovery in takotsubo syndrome (TTS) occurs over a wide‐ranging interval, varying from hours to weeks. We sought to investigate the clinical predictors and prognostic impact of recovery time for TTS patients. Methods and Results TTS patients from the International Takotsubo Registry were included in this study. Cut‐off for early LV recovery was determined to be 10 days after the acute event. Multivariable logistic regression was used to assess factors associated with the absence of early recovery. In‐hospital outcomes and 1‐year mortality were compared for patients with versus without early recovery. We analyzed 406 patients with comprehensive and serial imaging data regarding time to recovery. Of these, 191 (47.0%) had early LV recovery and 215 (53.0%) demonstrated late LV improvement. Patients without early recovery were more often male (12.6% versus 5.2%; P=0.011) and presented more frequently with typical TTS (76.3% versus 67.0%, P=0.040). Cardiac and inflammatory markers were higher in patients without early recovery than in those with early recovery. Patients without early recovery showed unfavorable 1‐year outcome compared with patients with early recovery (P=0.003). On multiple logistic regression, male sex, LV ejection fraction <45%, and acute neurologic disorders were associated with the absence of early recovery. Conclusions TTS patients without early LV recovery have different clinical characteristics and less favorable 1‐year outcome compared with patients with early recovery. The factors associated with the absence of early recovery included male sex, reduced LV ejection fraction, and acute neurologic events. Clinical Trial Registration URL: http://www.clinicaltrials.gov. Unique identifier: NCT01947621.